2005
DOI: 10.1007/s11661-005-0306-x
|View full text |Cite
|
Sign up to set email alerts
|

Improving the creep properties of 9Cr-3W-3Co-NbV steels and their weld joints by the addition of boron

Abstract: New ferritic steels with a controlled addition of boron have been developed recently for ultrasupercritical fossil power plants. These steels possess excellent creep resistance compared to conventional steels like P91, P92, P122, etc., and this has been attributed to the delay in coarsening of the carbides during creep owing to partial replacement of carbon by boron in these carbides. However, the susceptibility of the weld joints of the boron-containing ferritic steels to type IV cracking, which significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 13 publications
0
47
0
Order By: Relevance
“…An inspection of experimental results showed that the tempering embrittlement is attributed to the formation of the film-like M 23 (B·C) 6 phase on martensite/retained austenite boundaries in the temperature interval of 450-525°C. The 10%Cr steel exhibits very low toughness in a normalized state.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An inspection of experimental results showed that the tempering embrittlement is attributed to the formation of the film-like M 23 (B·C) 6 phase on martensite/retained austenite boundaries in the temperature interval of 450-525°C. The 10%Cr steel exhibits very low toughness in a normalized state.…”
Section: Discussionmentioning
confidence: 99%
“…1) A key issue for achieving a steam temperature ranging from 600 to 650°C and a steam pressure of about 30 MPa is the development of 10-12%Cr martensitic steels with a high creep strength and sufficient fracture toughness for the components of steam turbines such as rotors and rotating buckets/blades. 1) Boron containing 10-12%Cr steels with Co, W and Mo additives are attractive candidates for these crucial parts; [1][2][3][4][5][6][7][8] boron is considered as a very effective agent to enhance the creep strength. It is known [2][3][4][5][6][7][8][9][10] that the addition of boron decreases the coarsening of M23C6 carbides and leads to increased number density of these carbides because boron substitutes for carbon in M23C6, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recently developed ferritic 9Cr-3W-3Co-V-Nb steels with controlled additions of B and N have shown superior creep resistance at elevated temperatures compared to other conventional 9 wt.% Cr steels and are considered to be future candidates for 923 K (650°C) applications [3][4][5][6]. The microstructure of the 9Cr-3W-3Co-V-Nb steels after the pre-service heat treatment is generally similar to that of conventional 9-12 Cr steels, which typically exhibit a tempered martensite matrix with a fine dispersion of secondary phase particles [3,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high normalising temperature used with the 9Cr-3W-3Co-V-Nb steels, the prior austenite grain size of these steels after heat treatment is much larger compared to conventional 9-12 Cr steel. The large grain size is believed to be beneficial to the creep resistance of weld joints [4]. In addition to the large grain size, two of the important alloy design concepts behind the ferritic 9Cr-3W-3Co-V-Nb steels are: a) B is added to stabilise both Cr-rich carbides (M 23 C 6 ) against coarsening and grain boundaries during creep [10,11], and b) the addition of N is carefully controlled to produce a fine dispersion of MX (where M is V or Nb, and X is N or C) particles to strengthen the martensitic microstructure [10,11].…”
Section: Introductionmentioning
confidence: 99%